2022
DOI: 10.3390/joitmc8010007
|View full text |Cite
|
Sign up to set email alerts
|

International Open Innovation Strategies of Firms in European Peripheral Regions

Abstract: The involvement of companies in different open innovation activities, through knowledge outputs and inputs, has become increasingly important for the success of companies. However, the existing literature on open innovation is scarce concerning the internationalization process of companies. The internationalization of companies is fundamental in the continuous search to increase the performance of companies externally. The objective of the present research is to explain the strategic processes in the internati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 108 publications
0
10
0
Order By: Relevance
“…In the steel industry, to have a successful open business model which boasts innovativeness, it is very important to property link the current business model and perform an extensive review of the process of commercialization of the product to use the non-linearity of the innovation process. On this base, an organization can define its innovative abilities and define the moderators of the innovation process for particular steel industry enterprise [20,23].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the steel industry, to have a successful open business model which boasts innovativeness, it is very important to property link the current business model and perform an extensive review of the process of commercialization of the product to use the non-linearity of the innovation process. On this base, an organization can define its innovative abilities and define the moderators of the innovation process for particular steel industry enterprise [20,23].…”
Section: Discussionmentioning
confidence: 99%
“…Process (technological) innovation is a change in the company's manufacturing methods / methods of providing services, as well as in the ways of communicating to customers [20,21]. These methods may consist of changes in equipment or in the organisation of production; they may also be a combination of those two types of changes or result from the use of new knowledge [22][23][24]. They may aim to produce or provide new or improved products that could not be produced or they may aim to produce or deliver new or improved products that could not be produced or delivered by conventional methods [25].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Moreover, it allows the research to be carried out in the respondents' natural environment, enabling an inductive data analysis (Mohajan 2018). Thus, the exploratory case study is indicated to broaden the scope of research, enabling the emergence of particular patterns in a specific context (Lopes et al 2022).…”
Section: Methodology and Samplementioning
confidence: 99%
“…This approach is the most suitable for this study, as it allows for the in-depth study and understanding of a specific phenomenon in a particular context (Johnson and Duxbury 2010;Lopes et al 2021b;Yin 2018). The application of the exploratory qualitative method enables the broadening of the research objective and makes it possible to identify emerging patterns in specific contexts (Lopes et al 2022;Patton 2015), which is the case of the present study. We used multiple case studies to support the results (Yin 2018).…”
Section: Type Of Study and Cases Selectionmentioning
confidence: 99%